O currículo da disciplina de ciências da secretaria de educação do estado de São Paulo: compreensão e perspectiva dos professores - Vicente, Luciane da Silva (2017)
The present paper aims to study the current Science Curriculum of São Paulo Education Department (SEESP). It was implemented in 2008 with the purpose to unify the school programmers taught and improve the quality of education of state public schools. The curriculum was developed by a group of experts chosen by SEE without teachers’ participation. In this regard, the goal of the survey is to figure out how teachers comprehend the official curriculum and how this comprehension has been impacting their work. In order to reach the goal, the survey was organized in two different moments. The first one has a bibliographical process, in which part of the literature about approaches and conceptions of the Science Curriculum over the past few years was mapped. During this process, national and state Science curricular purposes produced from the 1990s were analyzed. We see Science teachers’ statements as an important instrument therefore, for the second moment, they were interviewed about their experience, perception, and comprehension about the curriculum and how it has impacted their teaching practice. The interviews were analyzed through articulation between qualitative research and content analysis methodology. The results achieved indicate that the official curriculum of the State of São Paulo ignores the peculiarities of different school contexts and it doesn’t provide appropriate teaching resources and infrastructure. Moreover, the state official curriculum conception turns teachers into mere repeaters of a curriculum built without the participation of those directly involved in teaching process.